2013
DOI: 10.1111/ped.12046
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic indicators of acute encephalopathy in patients with complex febrile seizures

Abstract: The development of neurologic damage in children with complex febrile seizures can be predicted within 6 h of onset, using the identified risk factors. The authors propose an assumption of severe febrile seizures (SFS) in children who fulfill these risk factors. Using SFS as an inclusion criterion, an interventional study for acute encephalopathy can be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 22 publications
2
51
0
2
Order By: Relevance
“…The consciousness disorders of AESD might be long because of the strong seizure itself and the secondary respiratory and cerebral circulation failure. A previous study reported that cases with a consciousness disorder lasting 12 h after FSE were at high risk of acute encephalopathy [11]. The previous study also reported that some AESD patients and patients who took long time to wake after seizures were in a state of non-convulsive status epileptics (NCSE) [12][13][14].…”
Section: Discussionmentioning
confidence: 94%
“…The consciousness disorders of AESD might be long because of the strong seizure itself and the secondary respiratory and cerebral circulation failure. A previous study reported that cases with a consciousness disorder lasting 12 h after FSE were at high risk of acute encephalopathy [11]. The previous study also reported that some AESD patients and patients who took long time to wake after seizures were in a state of non-convulsive status epileptics (NCSE) [12][13][14].…”
Section: Discussionmentioning
confidence: 94%
“…La crisis febril predominó, hallazgo también esperado (Relación 1,5:1 a favor de los niños), en el género masculino (59,9%) y en prematuros (45,3%), como consecuencia de la más lenta maduración del sistema nervioso (18,23,24) central en niños de este género y edad . El antecedente familiar (en primer grado) en este estudio parece tener poca importancia en niños con crisis febril, pues menos de 15% de los parientes refirieron presentar esta patología en su infancia, a pesar de ser considerada un trastorno genético (herencia dominante con penetrancia reducida o herencia poligénica), al punto de ser mayor en padres (se registran antecedentes entre 24-40%) y hermanos (se registran antecedentes entre 10-20%, e incluso hasta 80% en gemelos univitelinos) de los niños afectados.…”
Section: Discussionunclassified
“…Respecto al tratamiento anticonvulsivante de la crisis este se aplicó a 56,5% de los niños afectados, pero en ninguno se instauró el tratamiento de mantenimiento, a pesar de la amplia aceptación que se tiene de este como profiláctico sobre la repetición de las crisis febriles, porque, exclusivamente un tercio de los niños así tratados repetirán episodios posteriores, se cree que la negativa a la instauración sean los conocidos efectos adversos del uso crónico de dichas drogas y la experticia del galeno ante la particularidad de cada caso respecto a la consideración del riesgo de recurrencia y de desarrollo de secuelas en crisis (17,(31)(32)(33)(34) futuras , pero de ninguna manera debe ignorarse que la presencia de al menos dos de los siguientes antecedentes sí justifica fehacientemente el establecimiento de la terapia de mantenimiento; el inicio de la crisis durante el primer año de vida, las alteraciones en el examen neurológico y/o del desarrollo psicomotor, crisis prolongadas o atípicas, convulsiones previas con o sin fiebre y antecedentes de (15,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) convulsiones a febriles en los padres o hermanos .…”
Section: Discussionunclassified
“…In our previous study, we reported that children with acute encephalopathy without elevated aspartate aminotransferase (AST) levels within 6 h of onset were more likely to develop excitotoxic encephalopathy, whereas children with AST levels >90 IU/l within 6 h of onset were more likely to develop fulminant acute encephalopathy such as ANE or HSES [15]. In the current study, we excluded children with elevated AST levels to evaluate excitotoxic encephalopathy.…”
Section: Introductionmentioning
confidence: 93%
“…RSE was defined as a seizure or a sequence of intermittent seizures, persisting for at least 60 min, during which the child did not regain consciousness despite appropriate medical and antiepileptic drug (AED) therapy. Prolonged neurological abnormality was established by a Glasgow Coma Scale (GCS) score of <15 or the development of hemiplegia 6 h after onset [15].…”
Section: Patientsmentioning
confidence: 99%